Forensic pathology of fractures and mechanisms of injury postmortem CT scanning - Burke, Michael P. (CRC/Taylor & Francis, 2012)
Practitioners of forensic medicine have various tools at their disposal to determine cause of death, and today's computed tomography (CT) can provide valuable clues if images are interpreted properly. Forensic Pathology of Fractures and Mechanisms of Injury: Postmortem CT Scanning is a guide for the forensic pathologist who wants to use CT imaging to assist in determining the mechanism of injury that might have contributed to death.